Development of Mathematics Learning Media Based on Google Sites Contains Mathematical Literacy for Eighth Grade Junior High School Students - Dewi, Bela Saputri; Rusmining, Rusmining (Jurnal Pendidikan Matematika Universitas Lampung, 2025)
This study aims to develop a Google Sites-based mathematics learning medium that incorporates mathematical literacy within the topic of Relations and Functions for eighth-grade junior high school students, as well as to assess its validity and practicality. The background of the study stems from students' difficulties in understanding Relations and Functions, along with the need for learning media that can enhance both motivation and mathematical literacy skills. This research is a development study employing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) and was conducted at SMP Negeri 10 Yogyakarta. Data collection techniques included observations, interviews, and questionnaires, using instruments such as validation questionnaires completed by subject matter experts and media experts, as well as student response questionnaires administered to eighth-grade students at SMP Negeri 10 Yogyakarta. The study involved 5 students in a small group trial and 31 students in a large group trial. Evaluation results showed that the media met the “Good” criteria, with scores of 82.00 for the content aspect and 87.00 for the media aspect, indicating its suitability for use. Practicality testing with the small and large groups yielded an average score of 101.15, meeting the “Very Good” criteria. Therefore, this learning medium is considered valid and practical for use as an instructional tool for teaching Relations and Functions with integrated mathematical literacy.